The Application Of Reminiscence Therapy To The Support System Of The Elderly With Hypertension In An Effort To Improve The Quality Of Life In The Harjosari Village, Pekanbaru City: Penerapan Terapi Reminicence Pada Support Sistem Lansia Dengan Hipertensi Dalam Upaya Meningkatkan Kualitas Hidup Di Kelurahan Harjosari Kota Pekanbaru - Rusherina, Rusherina; Usraleli, Usraleli; Alkausyari, Alkausyari; Sartika, Dewi; Husnan, Husnan (Universitas Lancang Kuning, 2025)
The increase in the elderly population certainly raises various problems because the elderly experience various physical, mental, social and health changes. The aging process makes it difficult for the elderly to carry out Activity Daily Life (ADL) independently and become dependent on others. Limitations in performing ADLs, degenerative diseases, physical disability, pain, decreased cognitive function, sleep disturbances, social isolation, and life satisfaction can affect the quality of life of the elderly. Many elderly people find it difficult to adapt to the aging process, feel alone, frustrated, depressed and lose confidence, which affects their quality of life. The aging process causes various changes in humans including biological changes, psychological changes, social changes and spiritual changes. When the elderly try to adapt to the aging process they experience, not a few feel lonely, angry, depressed, and lose self-confidence. Reminiscence provides an adaptive function in the elderly and is positively correlated with successful adaptation through increased self-esteem, reaffirmation of a sense of identity, and mastery of their shortcomings in old age.